Computation of multidimensional poverty index: a case study - Mohammad, Aslam; T., Senthil Kumar; Sorooshian, Shahryar (The World Academy of Research in Science and Engineering, 2019)
Microfinance can play important role in alleviating poverty. Most marginal people have intention and capability to start small revenue generating activities. However, they are lack of finance to materialize their dreams. Microfinance may be one of the way for potential small entrepreneurs to acquire necessary inputs to start their activities. Government and international agencies are trying to eliminate poverty through microfinance programs, services and guidelines. This effort may be able to generate revenue and new jobs that can eradicate poverty. With this concept, Microfinance had been hosted primarily in Bangladesh and later replicated in other part of the world. Grameen Bank (GB) has been serving large number of people below poverty level in Bangladesh. However, both positive and negative impacts of microfinance on poverty have been visible in several studies that make microfinance still questionable. Therefore, this study intent to construct Multidimensional Poverty Index (MPI) measuring the incidence and intensity of the poverty among GB borrowers. It compares MPI of participant borrowers with non-participant borrowers of GB for observing the effect of microfinance. The results show that microfinance has positive impacts for participant borrowers as their index is relatively lower compared to non-participant borrowers. Hence, microfinance appears as an effective instrument for poverty alleviation. © 2019, World Academy of Research in Science and Engineering